Water Pollution and Water Quality Control of Selected Chinese Reservoir Basins - Huang, Tinglin (The Handbook of Environmental Chemistry, 2016)
This volume provides a detailed overview of water pollution and control of several selected Chinese reservoirs. It explores sediment contamination as well as algal blooms and their impact on water quality. Several chapters also discuss various methods of quality control, such as mixing-oxygenation combined with microbial remediation technologies. Due to their broad geographical distribution and different nutrition levels, the investigated reservoirs, the Jinpen, Shibianyu, Fenhe, Zhelin and Zhoucun reservoirs, can be regarded as representative for China. This comprehensive work will appeal to researchers, advanced students and reservoir managers.